Factors Associated with Utilization of 17-Hydroxyprogesterone Caproate for the Prevention of Recurrent Preterm Birth - DeNoble, Anna E.; Wynn, Clara E.; Weaver, Kristin E.; Wheeler, Sarahn M.; Swamy, Geeta K. (American Journal of Perinatology, 2020)
Objective Weekly 17-hydroxyprogesterone caproate (17OHP-C) from 16 to 36 weeks' gestation reduces the risk of recurrent spontaneous preterm birth (sPTB). Limited data suggest poor adherence to published guidelines. This study aimed to identify factors associated with 17OHP-C utilization.Study Design This retrospective cohort study included women with a singleton pregnancy who delivered within one academic health system between January 2014 and December 2015. Eligible women had a history of ≥1 singleton sPTB. Primary outcomes were counseling about, receipt of, and adherence to 17OHP-C therapy. Demographic and clinical predictors of the primary outcomes were determined using stepwise logistic regression.Results Of 410 eligible subjects, 69% (N = 284) were counseled about and 36% (N = 148) received 17OHP-C. Hispanic ethnicity, delay in prenatal care initiation, and a history of prior term births were associated with lower odds of 17OHP-C counseling. Each week delay in prenatal care initiation, Hispanic ethnicity, and each additional week's gestation of the earliest prior sPTB decreased the odds of receiving 17OHP-C. Maternal age and prior term births were associated with adherence.Conclusion Utilization of evidence-based 17OHP-C therapy remains suboptimal: cultural and access-to-care barriers for eligible women may impede efforts to decrease recurrent sPTB rates.
Keywords: 17-hydroxyprogesterone caproate; preterm birth; prevention; racially; ethnicity; access-to-care barriers